Stick out your tongue - Ma, Jian 1953- (Picador ; Farrar, Straus and Giroux, 2007)
A Chinese writer traveling in Tibet witnesses events that are enchanting and horrifying, beautiful and repulsive, including the sky burial of a young woman who died during childbirth and a nomad seeking forgiveness for incest